Religious Moderation for the Millennial Generation: An Islamic Education Perspective - Yusutria Yusutria; Charles Charles; Annur Fajri; Ahmad Taufik; Ahmad Jamil; M Amin (AT-TA'LIM, 2025)
The attitude of religious moderation is in the form of acknowledging the existence of other parties, being tolerant, respecting differences of opinion, and not imposing his will to use violence. This must be ingrained in the millennial generation of multicultural societies that share many traits. Diversity includes differences in culture, religion, race, language, ethnicity, tradition, etc. For example, in a multicultural society, tensions and conflicts between cultural groups often affect the harmony of life. This study explores religious moderation in the millennial generation from the perspective of Islamic education. This study uses the library research method in which the data comes from books, articles, and relevant scientific reports using the formulation of the problem. The collected data were analyzed using descriptive analysis techniques. This study shows that religious moderation is not religious moderation, but there must be moderation in attitudes toward diversity. From an Islamic education perspective, religious moderation is developed by starting from oneself, being instilled early, and setting an example for others. Of course, it is hoped that tasamuh, commitment, humanist, and wasatiyah education will become integrated, whole, and universal, all of which cannot be separated, mutually reinforcing, and mutually beneficial, as the best ummah and with broad scientific insight.